2012
DOI: 10.4049/jimmunol.1101755
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between Curdlan and GM-CSF Confers a Strong Inflammatory Signature to Dendritic Cells

Abstract: A simultaneous engagement of different pathogen recognition receptors provides a tailor-made adaptive immunity for an efficient defense against distinct pathogens. For example, cross-talk of TLR and C-type lectin signaling effectively shapes distinct gene expression patterns by integrating the signals at the level of NF-κB. In this study, we extend this principle to a strong synergism between the dectin-1 agonist curdlan and an inflammatory growth factor, GM-CSF. Both together act in synergy in inducing a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 55 publications
3
26
0
1
Order By: Relevance
“…In contrast to the suppressive activity of IFN-γ on CCL17 production, other cytokines have been reported to enhance CCL17, in particular IL-4, GM-CSF, and TNF, although this was also found to be cell type-dependent [5,25,26,29]. We therefore tested the ability of these cytokines to further induce CCL17 production in splenic DCs derived from either CCL17 E/+ -or CCL17 Figure 3A.…”
Section: Il-4 and Gm-csf Increase Ccl17 Production Of Splenic Dcs In mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the suppressive activity of IFN-γ on CCL17 production, other cytokines have been reported to enhance CCL17, in particular IL-4, GM-CSF, and TNF, although this was also found to be cell type-dependent [5,25,26,29]. We therefore tested the ability of these cytokines to further induce CCL17 production in splenic DCs derived from either CCL17 E/+ -or CCL17 Figure 3A.…”
Section: Il-4 and Gm-csf Increase Ccl17 Production Of Splenic Dcs In mentioning
confidence: 99%
“…In contrast to visceral and peripheral LN (PLN), the spleen harbors mainly lymphoid organ resident DCs with the exception of circulating plasmacytoid DCs [4]. Under inflammatory conditions monocytes are able to differentiate into mature DCs through the recognition of PAMPs in conjunction with GM-CSF (Csf-2) [5,6]. GM-CSF has been implicated in the formation of inflammatory DCs in vivo [7], and was also shown to enhance CD103 expression and the ability of CD8α + DCs to cross-present antigens to CD8 + T cells [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mucosal T cells. Min et al [41] found that curdlan has a synergistic effect with GM-CSF to promote the maturation of dendritic cells. In addition, Chiba et al [42] demonstrated that dectin-1 expressed by DCs and macrophages could recognize N-glycan structures on tumor cells and signals to activate IRF5 pathway, thereby activating NK cells to kill tumor cells.…”
Section: Discussionmentioning
confidence: 98%
“…Existem vários relatos de uma produção aumentada de citocinas frente a dois estímulos ao NF-κB, dando base para a afirmação supracitada (GAO et. al., 2001;MIN et. al., 2012).…”
Section: Secreção De Componentes Capsulares Auxilia O C Neoformans Aunclassified